Trends in Income Inequality and Economic Growth: a Bibliometric Analysis - Z. S. Temerbulatova; B. M. Mukhamediyev; J. Gazda (Экономика: стратегия и практика, 2022)
Despite the empirical and theoretical work that has been done, the impact of economic growth on income inequality remains a matter of debate, and conclusions regarding these relationships are still far from consensus. The review of the literature revealed that different model specifications, different datasets, and different estimation methods can influence the relationship between economic growth and income inequality. Moreover, when it comes to developing countries, the debate becomes even more intense, even if most authors argue that there is a negative relationship between them. This study aims to review the academic literature to identify key concepts and themes in the field of income inequality and its relationship to economic growth. Also, the purpose of the article is to identify gaps in this topic for future research. A bibliometric analysis of the literature was carried out using the R-package Biblioshiny tool. The sample includes 1 431 publications from the Scopus database. Articles are analyzed against annual scientific production, most important sources, most relevant organizations, a network of coincidences, and thematic mapping and evolution to understand trends in the body of knowledge about income inequality. As a result of the analysis, the main factors influencing economic growth, and subsequently the growth of income differentiation, were identified. A gap in the reviewed studies is the lack of knowledge of the factors determining the quality of economic growth, which subsequently affect income inequality. This research gap will be the direction of future research.